2022
DOI: 10.3390/polym14122346
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Molecular Structure and Mechanical Properties of κ-Carrageenan-Gelatin Hydrogel with Multi-Walled Carbon Nanotubes

Abstract: Hydrogels, three-dimensional hydrophilic water-insoluble polymer networks having mechanical properties inherent for solids, have attracted continuous research attention over a long time period. Here, we studied the structure and properties of hydrogel based on gelatin, κ-carrageenan and CNTs using the combination of SAXS, PXRD, AFM microscopy, SEM and rheology methods. We have shown that the integration of polysaccharide and protein in the composite hydrogel leads to suppression of their individual structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…On drying of -carrageenan@gelatin HDG, essential for the AFM experiment, from (Figure 25 a) the formation of the biopolymeric architecture is observed, referred as the biopolymeric scaffold [29]. For this composite HDG, the berous substrate initiating the gel formation are short when compared with those of pristine carrageenan solution (Figure 25 b) with a thickness of about 30 nm.…”
Section: Fmoc-ff and Cationic Peptides Multicomponent X-g Matrices Fo...mentioning
confidence: 98%
See 3 more Smart Citations
“…On drying of -carrageenan@gelatin HDG, essential for the AFM experiment, from (Figure 25 a) the formation of the biopolymeric architecture is observed, referred as the biopolymeric scaffold [29]. For this composite HDG, the berous substrate initiating the gel formation are short when compared with those of pristine carrageenan solution (Figure 25 b) with a thickness of about 30 nm.…”
Section: Fmoc-ff and Cationic Peptides Multicomponent X-g Matrices Fo...mentioning
confidence: 98%
“…The AFM image (Figure 25 c) is comprised of a network architecture of miniaturized aggregates within range of 70-100 nm in size. The AFM revealed that the nanotubes are evenly dispersed, being packed and in wrapping with biopolymeric matrices [29].…”
Section: Fmoc-ff and Cationic Peptides Multicomponent X-g Matrices Fo...mentioning
confidence: 99%
See 2 more Smart Citations
“…Proteins, possessing a positive net charge, form the coacervates with anionic polysaccharides. As we recently demonstrated on the example of lysozyme and κ-carrageenan coacervates [ 15 ], such interactions significantly modify the protein structure during the formation of bicomponent junctions and the common protein–polysaccharide structure [ 16 ]. On the other hand, the negatively charged globular proteins, trapped in the matrix of anionic polysaccharides upon the fast termination of the gelation process, usually retain their functional structure [ 2 ].…”
Section: Introductionmentioning
confidence: 99%